Prediction of bladder outcomes after traumatic spinal cord injury: a longitudinal cohort study - Pavese, Chiara; Weidner, Norbert; Rupp, Rüdiger (PLoS medicine, 2016)
Thomas Kessler and colleagues identify and validate two models to predict urinary continence and complete bladder emptying one year after traumatic spinal cord injury.
Gesehen am 04.04.2019